2014
DOI: 10.4103/0019-509x.151987
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and safety of early chest tube removal after complete video-assisted thoracic lobectomy

Abstract: Complete video-assisted thoracic lobectomy brings less drainage volume after operation. Early removal of chest tube in CVATL shows feasible and safe and demonstrates that it may reduce postoperative pain and help fast recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Excessively late removal of the thoracostomy tube may prolong patient discomfort associated with the thoracostomy tube itself, increase the risk of thoracostomy tube-related complications, and increase the cost of care and duration of hospitalization. Prospective studies of early removal protocols [20][21][22][23] in people have shown that thoracostomy tubes may be safely removed even with fluid production rates of 500 ml/day.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Excessively late removal of the thoracostomy tube may prolong patient discomfort associated with the thoracostomy tube itself, increase the risk of thoracostomy tube-related complications, and increase the cost of care and duration of hospitalization. Prospective studies of early removal protocols [20][21][22][23] in people have shown that thoracostomy tubes may be safely removed even with fluid production rates of 500 ml/day.…”
Section: Discussionmentioning
confidence: 99%
“…It is not routine at our institution to perform thoracic imaging or to evaluate the fluid cytologically prior to thoracostomy tube removal. In people, routine postoperative thoracic radiographs rarely lead to intervention, 21 and omitting this routine use has not been associated with an increase in morbidity or mortality. 39 The potential benefit of monitoring the cytological characteristics of pleural fluid could not be evaluated in this study due to inconsistent submission of samples to the laboratory, but there may be additional clinical value in this information that should be investigated in a future study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of thoracic drainage after lobectomy has been in the clinic for many years. By placing a closed chest drainage tube, it can achieve the effects of draining gas and fluids from the chest cavity, promoting lung expansion, preventing chest infections, and rebuilding negative pressure [27,28]. Meanwhile, by observing the amount, characteristics of drainages, and the fluctuation of the water column, some abnormal conditions can be found and treated in time [29].…”
Section: Discussionmentioning
confidence: 99%
“…1). [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] We searched the PubMed database with the following terms: VATS, video thoracoscopy, robot assisted, length of stay, complications, lung cancer, lung resection, and lobectomy. Only articles written in English were considered.…”
Section: End Pointmentioning
confidence: 99%